Numerical simulation of solar chimney integrated with exhaust of thermal power plant - Al-Kayiem, Hussain H. (WITpress, 2012)
• The heat losses within exhaust gases are an unavoidable part of operating any fuel-fired system. The flue gases still hold considerable thermal energy, which is exhausted to the atmosphere as waste heat and contributes to global warming. This paper presents a developed technique to enhance the performance of low temperature solar thermal systems by utilization of thermal energy recovery of flue gases. A CFD model was established based on the energy, momentum and mass conservation and the state equation in 2-D, steady assumption with kepsilon for the turbulence modelling using FLUENT - version 6.2.16 software. The model simulates the thermal and fluids flow processes in an inclined modified solar chimney. The flue inlet temperature was varied as, T f g= 603K, 843K, and 983K. The simulation results were validated by comparison with experimental results obtained from a lab scale model, and acceptable agreement was gained. When the flue temperature is increased from 605K to 843K, the performance is enhanced by 75%. The interesting find is that the efficiency of heat collection tends to increase as the absorber length increases up to a certain length, and then starts to decrease. In this study, the suitable dimension for solarflue gas collector is about 2.5 m